Clinicopathological Characteristics and Prognosis of HER2-Low Early-Stage Breast Cancer: A Single-Institution Experience - Xu, Hangcheng; Han, Yiqun; Wu, Yun; Wang, Yan; Li, Qing; Zhang, Pin; Yuan, Peng; Luo, Yang; Fan, Ying; Chen, Shanshan; Cai, Ruigang; Li, Qiao; et al. (Frontiers in Oncology, 2022)
Background HER2-low breast cancer, which is defined as HER2 1+ or 2+ in immunohistochemistry without gene amplification, accounts for a considerable part of all breast cancers. However, it remains controversial whether HER2-low breast cancer is a distinct entity. Our aim was to expound the clinical and pathological features of HER2-low early breast cancer as well as comparing the prognosis between HER2-zero and HER2-low early breast cancer. Methods The was a retrospective analysis that enrolled 1039 patients with available HER2 expression data in one single institute from 2013 to 2014, 262 HER2-positive patients of which was excluded from the subsequent analysis. The remaining patients were divided into HER2-zero and HER2-low groups. And each group was further categorized as HR-positive and HR-negative subgroups. Clinicopathological characteristics were collected and compared between HER2-zero and HER2-low groups. The primary endpoint was disease-free survival (DFS) and overall survival (OS), which was analyzed using the Kaplan-Meier method with log-rank test, landmark analysis and Cox proportional hazards model. Results A total of 777 non-HER2-positive patients were included in this analysis, among which 126, 552, 53, and 46 patients were HR-positive/HER2-zero, HR-positive/HER2-low, HR-negative/HER2-zero, and HR-negative /HER2-low, respectively. No significant difference in DFS and OS was detected between HER2-zero and HER2-low group when paired by HR status. Landmark analysis with a time point set at 5 years indicated that HR-positive/HER2-low patients had better DFS compared with HR-positive/HER2-zero patients after 5 years (P = 0.0047). HER2-low status was an independent prognostic factor for DFS after 5 years [hazard ratio (HR) 0.31, 95% confidence interval (CI) 0.13-0.75, P = 0.01]. Conclusion The prognosis of HER2-zero and HER2-low breast cancer was similar regardless of HR status. Patients with HR-positive/HER2-low tumors tended to have better DFS than HR-positive/HER2-zero counterparts after 5 years.